(untitled) (LEARNing Landscapes, 2018)
Technology can create new opportunities for learning with and from people of other cultures, not just about them. The Global Read Aloud (GRA) offers an example of such learning possibilities. The GRA is a project that connects classrooms via digital technologies to discuss common texts. This research explored the pedagogical opportunities and challenges associated with using technology to teach for global readiness in the GRA. Although technology broadened how and with whom GRA students read and discussed literature, the depth and quality of technology-facilitated teaching specifically for global readiness was somewhat unclear. We discuss implications for teaching for global readiness.